2007
DOI: 10.2147/copd.2007.2.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and control of influenza in persons with chronic obstructive pulmonary disease

Abstract: Despite recommendations for annual vaccination against influenza, more than half of patients with chronic obstructive pulmonary disease (COPD) in developed countries do not receive this vaccine. Influenza is characterized by its potentially of causing epidemics and by excess morbidity and mortality in patients with COPD and other chronic medical conditions. Good evidence of the efficacy, effectiveness, and cost-effectiveness of influenza vaccination underlines the recommendation of use in patients with COPD. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 68 publications
2
18
1
Order By: Relevance
“…This is consistent with some previous research which revealed that smokers are unlikely to receive influenza vaccine [23], even though they have a high risk of influenza virus infection [24] and chronic obstructive pulmonary disease (COPD). Patients with COPD are strongly encouraged to be vaccinated against influenza [25]. Such a result is not entirely surprising however, as smokers tend to have mixture of unhealthy behaviors; including lower vegetable intake and higher alcohol consumption when compared to non-smokers [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with some previous research which revealed that smokers are unlikely to receive influenza vaccine [23], even though they have a high risk of influenza virus infection [24] and chronic obstructive pulmonary disease (COPD). Patients with COPD are strongly encouraged to be vaccinated against influenza [25]. Such a result is not entirely surprising however, as smokers tend to have mixture of unhealthy behaviors; including lower vegetable intake and higher alcohol consumption when compared to non-smokers [26].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the risk of dying from acute myocardial infarction and chronic ischaemic heart disease is 1.3 times greater during influenza epidemic weeks [16]. Case fatality rates from Influenza A can be over 30% in persons with COPD compared to 0.1% or less in the healthy population [17]. Mortality rates in NCD patients range from ten to 377 per 100,000 influenza cases, depending on the number of high-risk conditions [18].…”
Section: Link Between Influenza and Ncdsmentioning
confidence: 99%
“…The severity of influenza infection or complications associated with it are greater in certain high risk groups 1315 . According to the CDC these groups include children younger than 5 years of age particularly affected the ones younger than 2 years old 16,17,18 elderly individuals 65 years old and above 19–23 , pregnant women 24,25 , and people with certain underlying medical conditions such as asthma 26,27 , chronic lung disease 28,29 , heart disease, diabetes 22,3032 , immunocompromised individuals 33,34,35 , and others 36 . Additionally, people who live in nursing homes and long-term care facilities 30,37,38 as well as health care workers 3942 are at high risk from influenza infection.…”
Section: 1 Influenza Virus and Influenza Vaccinationmentioning
confidence: 99%